2012
DOI: 10.2337/db11-1845
|View full text |Cite
|
Sign up to set email alerts
|

Increased Inner Ear Susceptibility to Noise Injury in Mice With Streptozotocin-Induced Diabetes

Abstract: We aimed to investigate the pathophysiology of diabetes-associated hearing impairment in type 1 diabetes using mice with streptozotocin-induced diabetes (C57BL/6J; male). Hearing function was evaluated 1, 3, and 5 months after induction of diabetes (five diabetic and five control animals per time point) using auditory-evoked brain stem responses (ABRs). Mice (four diabetic and four control) were exposed to loud noise (105 dB) 5 months after induction of diabetes. ABRs were measured before and after noise expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…SGC density was determined as the number of cell nuclei per 10000 μm2 of Rosenthal’s canal. We calculated SGC density as described previously [ 16 ] in three mid-modiolar sections at 30 μm apart from each cochlea, with the average value used for each mouse.…”
Section: Methodsmentioning
confidence: 99%
“…SGC density was determined as the number of cell nuclei per 10000 μm2 of Rosenthal’s canal. We calculated SGC density as described previously [ 16 ] in three mid-modiolar sections at 30 μm apart from each cochlea, with the average value used for each mouse.…”
Section: Methodsmentioning
confidence: 99%
“…Myers and his group had previously described morphological changes in the utricle and saccule as well. 30,31 Summary of Animal Studies Evidence for increased risk of noise and agerelated neuropathology also has been demon-strated in DM animal models 9,17,25 and is consistent with the prolonged latency and decreased amplitude of the ABR in humans with DM. 32 Possible mechanisms proposed included microangiopathy, abnormal accumulation of metabolic by-products due to mitochondrial dysfunction (e.g., oxidative stress), glutathione dysregulation, glycation, and protein synthesis dysfunction.…”
Section: Vestibular Impairment and Diabetes Mellitusmentioning
confidence: 64%
“…Wu et al 9 found that rats (STZ injected) with DM demonstrated impaired recovery from a noise-induced temporary threshold shift (TTS); this recovery was improved to control levels with insulin treatment. Fujita et al 25 showed significant changes to spiral ganglion despite preservation of hair cells following a TTS-inducing noise exposure in DM rats compared with controls.…”
Section: Noise and Diabetes Mellitus Interactionmentioning
confidence: 98%
“…Diabetes mellitus–related microvascular diseases of the cochlea may lead to hearing impairment. In streptozotocin‐induced diabetic animals, thickened basement membranes in the capillaries of the stria vascularis and thickened vessel walls in the modiolus have been observed . Anatomic pathological studies of human temporal bones have demonstrated that diabetes mellitus results in microangiopathic changes of the cochlea, including atrophy of the stria vascularis and vascular involvement in the basilar membrane, although epidemiological evidence suggesting any causal link between diabetes mellitus and hearing impairment is sparse.…”
Section: Discussionmentioning
confidence: 99%